Effects of alternate wetting and drying or low light intensity factors on increasing grain yield and 2AP content in fragrant rice - Noynay, Jerico; Chutteang, Cattleya; Chompoo, Jamnian; Pornprom, Tossapon; Malumpong, Chanate (Agriculture and Natural Resources, 2026)
Importance of the work: Alternating wetting and drying (AWD) is a technology that can save water without affecting yield and may increase the 2-acetyl-1-pyrroline (2AP) content. Furthermore, low light intensity (LL) may reduce yield but increase the 2AP content. Objectives: To investigate the effects of AWD and LL conditions and their interactions on Hom Malaiman (HMM) aromatic rice variety in paddy fields. Materials and Methods: HMM was grown over three consecutive seasons. A randomized complete block split plot design was used to investigate water management (continuous flooding (CF) and AWD) and light intensity (natural light (NL) and low light) conditions. Results: Water management (W) and light conditions (L) affected agronomic, physiological and grain quality traits. The W × L interaction had significant effects on grain yield and 2AP content. AWD significantly increased the grain yield by 16.31% compared to the CF condition, whereas LL decreased the grain yield by 16.00% compared to the NL condition. AWD × NL resulted in the highest grain yield, whereas CF × LL resulted in the lowest yield. AWD and LL increased the 2AP content in rice grains by 3.22% and 8.28%, respectively. In addition, AWD × LL produced the highest 2AP content, whereas CF × NL produced the lowest 2AP content. Main finding: The interaction between AWD and LL may not be suitable for increasing yield together with increasing the 2AP content. In addition, the influence of LL was greater than that of AWD in terms of increasing the 2AP content